2016
DOI: 10.1080/10803548.2016.1153858
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to electric and magnetic fields during tasks at ground or floor level at 110 kV substations in Finland

Abstract: The aim was to investigate occupational exposure to electric and magnetic fields during tasks at ground or floor level at 110 kV substations in Finland and to compare the measured values to Directive 2013/35/EU. Altogether, 347 electric field measurements and 100 magnetic field measurements were performed. The average value of all electric fields was 2.3 kV/m (maximum 6.4 kV/m) and that of magnetic fields was 5.8 µT (maximum 51.0 µT). It can be concluded that the electric and magnetic field exposure at ground … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…With the rapid implementation of ultra high-voltage and extra high-voltage power grid, the electromagnetic environment around the power transmission line, substation and high-voltage equipment becomes worse and more complex. It has been investigated that the power-frequency electric field can cause damages to human body [1][2][3]. The general public is becoming increasingly concern about potential health hazards of exposure to the electromagnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid implementation of ultra high-voltage and extra high-voltage power grid, the electromagnetic environment around the power transmission line, substation and high-voltage equipment becomes worse and more complex. It has been investigated that the power-frequency electric field can cause damages to human body [1][2][3]. The general public is becoming increasingly concern about potential health hazards of exposure to the electromagnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…High-voltage equipment is always surrounded by a strong electric field, and studies have shown that power frequency electric fields have potential harmful effects on human health and safety [ 1 , 2 , 3 ]. An extremely high power frequency electric field will cause electrostatic discharge or even transient electric shock, and this will lead to other, more serious safety incidents.…”
Section: Introductionmentioning
confidence: 99%